2017
DOI: 10.1016/j.ajhg.2017.01.003
|View full text |Cite|
|
Sign up to set email alerts
|

De Novo Disruption of the Proteasome Regulatory Subunit PSMD12 Causes a Syndromic Neurodevelopmental Disorder

Abstract: Degradation of proteins by the ubiquitin-proteasome system (UPS) is an essential biological process in the development of eukaryotic organisms. Dysregulation of this mechanism leads to numerous human neurodegenerative or neurodevelopmental disorders. Through a multi-center collaboration, we identified six de novo genomic deletions and four de novo point mutations involving PSMD12, encoding the non-ATPase subunit PSMD12 (aka RPN5) of the 19S regulator of 26S proteasome complex, in unrelated individuals with int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 64 publications
5
77
0
4
Order By: Relevance
“…The presence of cardiac, renal, genital, and ophthalmological defects and seizures were more commonly seen in individuals with PSMD12 mutations while microcephaly was more commonly associated with a BPTF disruption. Notably, Küry et al 39 also reported that individuals with 17q24.2 deletions involving PSMD12 and BPTF had more prominent microcephaly than those with isolated PSMD12 deficiency, supporting further the causative role of BPTF in microcephaly.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…The presence of cardiac, renal, genital, and ophthalmological defects and seizures were more commonly seen in individuals with PSMD12 mutations while microcephaly was more commonly associated with a BPTF disruption. Notably, Küry et al 39 also reported that individuals with 17q24.2 deletions involving PSMD12 and BPTF had more prominent microcephaly than those with isolated PSMD12 deficiency, supporting further the causative role of BPTF in microcephaly.…”
Section: Discussionmentioning
confidence: 79%
“…Recently, we have reported de novo disruption of the proteasome regulatory subunit PSMD12 (MIM: 604450). 39 Reported subjects included four (individuals 1-4) with single-nucleotide variants in PSMD12, three (individuals 5, 7, and 9) with CNV deletions on 17q24.2 affecting PSMD12, BPTF, and other genes, and two (individuals 8 and 10) with deletions on 17q24.2 encompassing PSMD12 and neighboring genes but leaving BPTF intact. 39 We hypothesize that the clinical phenotype of 17q24.2 microdeletion is associated with haploinsufficiency of the affected PSMD12 and/or BPTF, and possibly additional genes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations